Asthma control and severe exacerbations in patients with moderate or severe asthma in Jilin Province, China: a multicenter cross-sectional survey. Issue 1 (December 2016) - Yan, Bing-di; Meng, Shan-shan; Ren, Jin; Lv, Zheng; Zhang, Qing-hua; Yu, Jin-yan; Gao, Rong; Shi, Chang-min; Wu, Chun-feng; Liu, Chun-lin; Zhang, Jie; Ma, Zhong-sen; et al.
Abstract Background No systemic evaluation of asthma control in Jilin Province has been reported. Asthma control might provide the basis for asthma management in this region. A multicenter hospital-based cross-sectional study was performed to investigate the asthma control and related factors for severe asthma exacerbations in patients with moderate or severe asthma in Jilin Province, China. Methods The study enrolled 1546 patients in five grade one general hospitals from January to December 2013. Asthma medication, patient self-management, asthma control test (ACT) scores and frequency of severe asthma exacerbations during the follow-up (12 months) were collected via a follow-up questionnaire. Results In the study, 889 patients provided a complete follow-up questionnaire. Severe asthma exacerbations occurred in 54.89 % of patients. ACT score ≤15, asthma medication ≤ 3 months, severe asthma, income level lower than average Per Capita Disposable Income (PCDI) and a lower educational level were risk factors of a severe exacerbation. Conclusions Poor adherence to asthma medication, poor asthma symptom control, lower income, a low educational level might be possible reasons for the high incidence of severe asthma exacerbations and poor asthma control in Jilin Province of China.